Analisis Efektivitas Biaya Pengobatan Kombinasi Zidovudin, Lamivudin, Nevirapin dan Kombinasi Tenofovir, Lamivudin, Efavirenz Pada Pasien HIV/AIDS di RSUD Kota Bekasi - Yusi Anggriani; Fredrick D. Purba; Reise Manninda; Tarsinah Tarsinah (Fakultas Farmasi Universitas Pancasila, 2020)
HIV/AIDS has become a global issue in many countries. The implementation of ARV / HAARTprograms is always changing, due to clinical reasons, population factors, and aff ordability. Pharmacoeconomic studies can be one of the considerations in the policy process for procurement and selection of therapy regimens. The aims of this study were to determine the eff ectiveness of treatment based on CD4 increase and cost eff ectiveness analysis of HAART A and HAART B treatment regimens. This study used a cross sectional observation method. Retrospective data collection and non-experimental observation where conducted followes by a quantitative descriptive analysis according to the patient's perspective to obtain costeffectiveness data. Data were statistically analyzed to obtain the cost-eff ectiveness of treatment. The results showed that the cost-eff ectiveness analysis (CEA) of two regimens found that HAART A was more dominant than HAART B with a signifi cant diff erence p<0.05. While ACER regimen HAART A (16,227) was greater than the value ACER therapy B (28,330.7).